Blue lightning eaudiobook - Cleeves, Ann (Shetland Island, 2015)
Blue Lightning is the fourth in a stellar suspense series from Ann Cleeves set on the Shetland Islands, the basis for the hit BBC show Shetland, starring Douglas Henshall. Inspector Jimmy Perez takes his fiancé home to Fair Isle, the tiny island he comes from, to meet his parents. The island is a magnet for bird watchers, who congregate at the local inn and lighthouse. When a local married celebrity, who had an eye for the lads, is murdered, Perez discovers that the suspects are very close to him indeed. With a sensational ending destined to create much buzz in the mystery world, Blue Lightning will thrill suspense fans everywhere.